Effect of measurement of non-destructive firmness on Tomato quality and comparison with destructive methods - Ranatunga, C.L.; Hiran H. E. Jayaweera; Suraweera, S.K.K.; Ariyaratne, T.R. (My University, 2009)
Almost all instrumental non-destructive (ND) type firmness test methods which involve a physical contact with the tomato when used for testing, deliver at least a minute damage to the fruit. The damage induced on a fruit was estimated when a so-called non-destructive firmness test was performed repeatedly on tomato fruit. The common method of firmness testing uses Magness-Taylor (MT) type firmness tester and in this destructive type test method, after having peeled, the tomato pulp is pierced with a probe. Qualitest (HPE-ll-FFF model) tester and the Bishop (FT 327 model) tester were used as ND and MT type firmness testers, respectively. Tomato variety “Rajitha” grown in Rathkinda area in Matale, during Maha season (Sept 2008) was subjected to this investigation. In a series of repeated ND type firmness test , a loss of firmness of 9.5 % was observed between the fi rst and the second measurement, regardless the ripeness level of tomato. At lower ripeness leve ls, tomato exhibited an exponential decay in percentage loss of firmness when subjected to repeated ND test, while red-ripe tomatoes demonstrated a slightly deviated behaviour. A study on the behaviour of MT vs. ND type firmness suggests a good linear relationship with a non-zero intercept. The relationship proposes a ND type firmness of 0.405 kg for a tomato which registers zero MT type firmness. Hence the contribution of the peel to th e ND type firmness would be 0.405 kg.
Keywords: Effect of measurement of non-destructive firmness on Tomato quality and comparison with destructive methods